Luces y sombras de la política de la competencia en Italia - Berumen, Sergio A. (2008)
In the past the responsible authorities of the Italian government have limited their performance to react to those pressures coming from the European Commission in respect to competence matters, but only in some exceptional circumstances the different Italian governments have acted in a reactive way. In this article it is demonstrated that the Italian policies regarding competence have been erratic; sometimes the authorities have reacted in time, but in some other occasions their intervention was quite urgent and it has arrived later than it was expected. To this effect, interest is focused in analyzing the evolution of the market and in pointing out the most significative advances that have been reached in respect to their internal market liberalization.